The Dynamics Marriage Readiness of Muslim Adolescent from the Perspective of Psychology and Islamic Law - Eka Sufartianinsih Jafar; Andi Yaqub (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The high rate of divorce in young couples is motivated by psychological and spiritual unpreparedness. Premarital education is a resolution to minimize the divorce rate. This study aims to hack the knowledge and understanding of Muslim adolescents regarding marriage and marriage readiness from a psychology and Islamic law perspective. This type of research uses a descriptive quantitative data collection method using a survey in the form of a questionnaire. The research subjects were 820 adolescents aged 15-20 years who came from various levels of education, namely senior high school students (54.5%) and undergraduate students (45.5%). The results of this study indicate that there are several motivations for marriage for Muslim adolescents, namely (1) wanting to justify themselves by 49% (2) wanting to get attention and affection by 20.5%, (3) wanting to have children by 15.6%, (4) improve the economy by 10%, (5) follow parents wishes 4.9%. While the things that teenagers need to prepare for marriage are (1) Economy by 31.9%, (2) Studying Religion by 29.4%, (3) Education by 20.7%, and (4) Improving Character 18%. Adolescent understanding is still low on the purpose of marriage and the forms of marriage readiness. Indicated by the orientation and motivation of marriage is dominated by the fulfillment of biological and material needs. The implication of this research is to be able to provide a comprehensive view in terms of marriage readiness from the point of view of psychology and Islamic law as reference material for providing premarital preparation/premarital education to adolescents so that they can prepare for married life.